Perlindungan Hukum Terhadap Hak Dan Kewajiban Antara Pt Migo Anugerah Sinergi Dengan Para Pihak Dalam Perjanjian Kemitraan - Azdho Muhamad Ramadhon; Soefyanto Soefyanto; Nisrina Mutiara Dewi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The purpose of this thesis is to establish and define the kind of legal protection that will be provided to the parties bound by the PT Migo Anugerah Sinergi partnership agreement in order for them to fulfill their rights and obligations. PT Migo Anugerah Sinergi has entered into an agreement with Migo Station, which serves as its partner, to explain the rights and obligations of the parties regarding legal protection in the event of a loss, as well as the type of legal protection that will be provided to them by the Migo Ebike transportation service provider, in order to better understand the implementation or application of the agreement. As a result of their participation in the partnership arrangement, they have suffered losses. Because the relationship between PT. Migo Anugerah Synergy and Migo Station is not only established in writing through a partnership/cooperation agreement, but it is also established through an electronic agreement, both parties are required to approve and sign the electronic agreement. A qualitative research approach is used in this study, which employs a normative empirical approach based on Indonesian laws and regulations, specifically Article 1 paragraph (13) and Article 11 of the Law of the Republic of Indonesia Number 20 of 2008 concerning Micro, Small, and Medium-Sized Enterprises and Article 4, Article 5, Article 6, and Article 7 of the Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection and Article 4, Article 5, and Article 6 of the Law of the Republic of Indonesia Number 11 of 2016 concerning Small and Medium-Sized.